Principles of respiratory tract infection rational antibiotic therapy - Oksana V. Fesenko (LLC "MEDIAFORMAT", 2021)
Continuously increasing resistance of infectious agents together with rapid decrease in the number of novel antibacterial drugs makes the rational antibiotic selection one of the important challenges facing modern medicine. The urgency of the issue is also growing because of strategic and tactical mistakes in treatment of respiratory tract infections significantly affecting the disease outcome. The paper reports principles of respiratory tract infection antibiotic therapy based on contemporary federal guidelines on management of infectious respiratory tract diseases. Clinical example of rational antibiotic therapy selection in patient with community-acquired pneumonia is provided.